A gas diffusion layer with a gradient pore structure and a method for manufacturing the same

CN120844109BActive Publication Date: 2026-10-09NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511063505.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2026-10-09
Estimated Expiration
2045-07-31

AI Technical Summary

Technical Problem

但过小的孔易被水淹没或被气泡阻塞,阻碍传质,导致深层催化剂无法接触反应物而利用率骤降;过大的孔则显著降低比表面积和有效载铂量

Benefits of technology

1、本发明通过在钛菱形网上依次喷涂含粗、细粒度球形钛粉的浆料并烧结,获得具有第一微孔层、第二微孔层的梯度孔结构的气体扩散层,利用钛菱形网保证气体扩散层的机械强度,防止微孔层在装配或服役过程中发生变形,同时还能够有利于气液传输,利用大孔径的第二微孔层保证气体扩散层良好的气液传输,利用小孔径的第一微孔层保证气体扩散层与催化剂层的充分接触,提高了催化剂利用率。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a gas diffusion layer with gradient pore structure and a preparation method thereof, and the preparation method comprises the following steps: 1, immersing titanium rhombus net into liquid paraffin; 2, uniformly mixing anhydrous ethanol, tributyl phosphate, polyvinyl butyral and two kinds of spherical titanium powder with different particle sizes to prepare a second slurry containing coarse-grained spherical titanium powder and a first slurry containing fine-grained spherical titanium powder, and spraying the two slurries on the surface of the titanium rhombus net filled with paraffin in sequence; 3, performing debinding and sintering on the sprayed titanium rhombus net to obtain the gas diffusion layer with gradient pore structure. The slurry containing coarse-grained and fine-grained spherical titanium powder is sprayed on the titanium rhombus net in sequence, and then sintering is performed, so that the gas diffusion layer with gradient pore structure is obtained, the gas diffusion layer has high catalyst utilization rate, high mechanical strength and good gas-liquid transmission, the structure can be adjusted according to actual working conditions to regulate the performance of the gas diffusion layer, and the application is suitable for the field of PEM electrolysis hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water electrolysis for hydrogen production technology, specifically relating to a gas diffusion layer with a gradient pore structure and its preparation method. Background Technology

[0002] The gas diffusion layer (GDL) is a core component of a proton exchange membrane (PEM) electrolyzer, located between the catalyst layer and the bipolar plates. Its primary function is to achieve efficient and uniform transfer of reactants (liquid water) to the catalyst layer while simultaneously promoting the rapid expulsion of product gases (oxygen at the anode and hydrogen at the cathode), preventing bubble accumulation and blockage of the reaction interface. Furthermore, the GDL must possess excellent electrical conductivity to conduct current, good thermal conductivity to aid heat dissipation, and provide necessary mechanical support to protect the catalyst layer and membrane. To achieve these functions, the GDL must have a suitable pore structure distribution and good gas-liquid transport capabilities. Crucially, the anode GDL, due to its highly oxidizing environment, is typically made of platinum-plated titanium-based material. The structure and performance of the GDL directly determine the mass transfer efficiency, ohmic loss, and overall operational stability of the electrolyzer.

[0003] The thickness and pore size of the gradient pore structure (GDL) have complex and critical effects on its performance. Increasing thickness generally improves mechanical stability, better resists assembly pressure and operating stress, and protects core components. However, excessive thickness increases pore tortuosity, hinders gas-liquid transport, and significantly increases platinum loading. On the other hand, pore size and distribution profoundly affect catalyst utilization and gas-liquid transport efficiency. Large pores facilitate rapid discharge of gaseous products (O2 / H2) and supply of liquid water, reducing blockage; small pores provide high specific surface area for highly dispersed catalyst loading, increasing active site density. However, pores that are too small are easily submerged by water or blocked by bubbles, hindering mass transfer and causing deep catalysts to fail to contact reactants, resulting in a sharp drop in utilization; pores that are too large significantly reduce specific surface area and effective platinum loading. Therefore, it is urgent to design an optimized gradient pore structure and explore preparation methods to achieve a dynamic balance between high catalyst utilization, efficient gas-liquid transport, and strong mechanical stability, which is key to improving the performance of PEM electrolyzers and reducing costs. Summary of the Invention

[0004] The technical problem to be solved by this invention is to address the shortcomings of the prior art by providing a method for preparing a gas diffusion layer with a gradient pore structure. This method involves sequentially spraying a slurry containing coarse and fine-grained spherical titanium powder onto a titanium rhomboid mesh and then sintering it to obtain a gas diffusion layer with a gradient pore structure having a first microporous layer and a second microporous layer. This allows each structure to function effectively, ensuring that the gas diffusion layer has high catalyst utilization, high mechanical strength, and good gas-liquid transport, thereby improving the hydrogen production efficiency of PEM electrolyzers and reducing costs.

[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: a method for preparing a gas diffusion layer with a gradient pore structure, characterized in that the gas diffusion layer is composed of a first microporous layer, a second microporous layer, and a titanium rhombic mesh support layer bonded by metallurgy, and the method for preparing the gas diffusion layer includes the following steps: Step 1: Immerse the titanium rhombus mesh in liquid paraffin at 70℃~100℃, remove it, cool it, and clean the surface to obtain a titanium rhombus mesh filled with paraffin. Step 2: Mix anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and two types of spherical titanium powder with different particle sizes evenly to prepare slurry No. 1 containing fine-grained spherical titanium powder and slurry No. 2 containing coarse-grained spherical titanium powder. Then, use a spray gun to spray slurry No. 2 and slurry No. 1 onto the surface of the titanium rhombus mesh filled with paraffin in step 1 to obtain the sprayed titanium rhombus mesh. Step 3: The sprayed titanium rhomboid mesh obtained in Step 2 is degreased and sintered in one step to form a first microporous layer with small pore size and a second microporous layer with large pore size, which are then cooled in the furnace to obtain a gas diffusion layer with a gradient pore structure.

[0006] The method for preparing a gas diffusion layer with a gradient pore structure is characterized in that, in step two, the concentration of tributyl phosphate in slurry No. 1 and slurry No. 2 is 0.005 g / mL to 0.03 g / mL, the concentration of polyvinyl butyral is 0.03 g / mL to 0.15 g / mL, and the concentration of spherical titanium powder is 0.5 g / mL to 1.5 g / mL.

[0007] The method for preparing a gas diffusion layer with a gradient pore structure is characterized in that the particle size of the spherical titanium powder in the first slurry is 0.1µm~15µm, and the particle size of the spherical titanium powder in the second slurry is 20µm~50µm.

[0008] The method for preparing a gas diffusion layer with a gradient pore structure described above is characterized in that, in step three, the heating rate for the one-step degreasing and sintering process is 0.5℃ / min to 2℃ / min, the degreasing temperature is 250℃ to 450℃, the degreasing time is 1h to 10h, the sintering temperature is 800℃ to 1200℃, the sintering time is 0.5h to 8h, and the vacuum degree does not exceed 1×10⁻⁶. -2 Pa.

[0009] Meanwhile, this invention also discloses a gas diffusion layer with a gradient pore structure prepared according to the above method, characterized in that the total thickness of the gas diffusion layer is 120µm~600µm, the thickness of the first microporous layer is 10µm~50µm with an average pore size of 2µm~10µm, the thickness of the second microporous layer is 10µm~50µm with an average pore size of 5µm~30µm, and the thickness of the titanium rhombic mesh support layer is 100µm~500µm with a mesh size of 0.5mm×1mm~3mm×5mm. The mesh size is the length of the two diagonals of the titanium rhombic mesh.

[0010] Compared with the prior art, the present invention has the following advantages: 1. This invention obtains a gas diffusion layer with a gradient pore structure consisting of a first microporous layer and a second microporous layer by sequentially spraying a slurry containing coarse and fine-grained spherical titanium powder onto a titanium rhomboid mesh and sintering it. The titanium rhomboid mesh ensures the mechanical strength of the gas diffusion layer and prevents deformation of the microporous layer during assembly or service, while also facilitating gas-liquid transport. The large-pore second microporous layer ensures good gas-liquid transport in the gas diffusion layer, while the small-pore first microporous layer ensures sufficient contact between the gas diffusion layer and the catalyst layer, thereby improving catalyst utilization.

[0011] 2. In this invention, the titanium rhomboid mesh is first filled with paraffin wax to prevent the slurry from seeping in during subsequent spraying, and the degreasing and sintering are removed to ensure that the mesh openings of the titanium rhomboid mesh in the product are unobstructed, thereby ensuring the high gas-liquid transport efficiency of the gas diffusion layer and providing mechanical support for the microporous layer on its surface, thus ensuring the strength of the gas diffusion layer.

[0012] 3. By controlling the concentrations of tributyl phosphate, polyvinyl butyral, and spherical titanium powder in each slurry, and by controlling the particle size of the spherical titanium powder in each slurry, the present invention effectively regulates the thickness and pore size of the first and second microporous layers to ensure the formation of a gradient pore structure, thereby adjusting the performance of the gas diffusion layer.

[0013] 4. By controlling the heating rate, degreasing temperature, and time of the one-step degreasing and sintering process, this invention ensures the complete removal of paraffin wax filled in the titanium rhomboid mesh and organic matter in the sprayed slurry. By controlling the sintering temperature, time, and vacuum level, a good metallurgical bond is achieved between the microporous layer and the titanium rhomboid mesh, thereby ensuring the service life of the gas diffusion layer.

[0014] 5. In the gas diffusion layer of the present invention, the thickness of the first microporous layer and the second microporous layer is only 10µm~50µm, which effectively reduces the surface area of ​​subsequent platinum plating, thereby significantly reducing the amount of platinum plating and reducing costs. At the same time, the actual contact area between the small-diameter first microporous layer and the catalyst layer increases after it is assembled into the electrolytic cell, effectively improving the catalyst utilization rate. The filaments of the titanium rhombic mesh support layer are dense and dispersed, and have higher mechanical strength than the microporous layer. They also form a metallurgical bond with the microporous layer, which not only provides mechanical support, but also further improves the gas-liquid transport efficiency due to the larger mesh pore size than the microporous layer.

[0015] 6. The gas diffusion layer with gradient pore structure of the present invention can be flexibly adjusted in terms of thickness, pore structure and mechanical strength according to actual working conditions, which is convenient to operate and easy to implement.

[0016] The technical solution of the present invention will be further described in detail below through embodiments. Detailed Implementation

[0017] Example 1 The gas diffusion layer in this embodiment consists of a first microporous layer, a second microporous layer, and a titanium rhombic mesh support layer bonded together by metallurgy. The preparation method of this gas diffusion layer includes the following steps: Step 1: Immerse the titanium rhombus mesh in liquid paraffin at 70℃~100℃, remove it, cool it, and clean the surface to obtain a titanium rhombus mesh filled with paraffin. Step 2: Mix anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and two types of spherical titanium powder with different particle sizes evenly to prepare slurry No. 1 containing fine-grained spherical titanium powder and slurry No. 2 containing coarse-grained spherical titanium powder. The concentrations of tributyl phosphate, polyvinyl butyral, and spherical titanium powder in slurry No. 1 and No. 2 are both 0.005 g / mL, 0.03 g / mL, and 0.5 g / mL, respectively. The particle size of the spherical titanium powder in slurry No. 1 is 12µm~15µm, and the particle size of the spherical titanium powder in slurry No. 2 is 46µm~50µm. Then, use a spray gun to spray slurry No. 2 and slurry No. 1 onto the surface of the titanium rhomboid mesh filled with paraffin in step 1 to obtain the sprayed titanium rhomboid mesh. Step 3: The coated titanium rhomboid mesh obtained in Step 2 is then subjected to a vacuum of 2.8 × 10⁻⁶. -3 Under Pa conditions, the material is heated to 250℃ at a rate of 0.5℃ / min and held for 1 hour for degreasing. Then, it is heated to 800℃ and held for 8 hours for sintering, so that the No. 1 slurry and the No. 2 slurry form a first microporous layer with small pore size and a second microporous layer with large pore size. The material is then cooled with the furnace to obtain a gas diffusion layer with a gradient pore structure.

[0018] Upon testing, the total thickness of the gas diffusion layer prepared in this embodiment is 120µm, the thickness of the first microporous layer is 10µm with an average pore size of 9µm, the thickness of the second microporous layer is 10µm with an average pore size of 28µm, and the thickness of the titanium rhombic mesh support layer is 100µm with a mesh size of 3mm×5mm.

[0019] Example 2 The difference between this embodiment and Embodiment 1 is that in step two, the concentration of tributyl phosphate in slurry No. 1 and slurry No. 2 is 0.015 g / mL, the concentration of polyvinyl butyral is 0.09 g / mL, and the concentration of spherical titanium powder is 1.1 g / mL. The particle size of the spherical titanium powder in slurry No. 1 is 8 µm to 11 µm, and the particle size of the spherical titanium powder in slurry No. 2 is 32 µm to 37 µm.

[0020] Upon testing, the total thickness of the gas diffusion layer prepared in this embodiment is 306µm, the thickness of the first microporous layer is 24µm with an average pore size of 5µm, the thickness of the second microporous layer is 22µm with an average pore size of 15µm, and the thickness of the titanium rhombic mesh support layer is 260µm with a mesh size of 1mm×2mm.

[0021] Example 3 The difference between this embodiment and Embodiment 1 is that in step two, the concentration of tributyl phosphate in slurry No. 1 and slurry No. 2 is 0.03 g / mL, the concentration of polyvinyl butyral is 0.15 g / mL, and the concentration of spherical titanium powder is 1.5 g / mL. The particle size of the spherical titanium powder in slurry No. 1 is 5 µm to 8 µm, and the particle size of the spherical titanium powder in slurry No. 2 is 20 µm to 25 µm.

[0022] Upon testing, the total thickness of the gas diffusion layer prepared in this embodiment is 588µm, the thickness of the first microporous layer is 48µm with an average pore size of 2µm, the thickness of the second microporous layer is 50µm with an average pore size of 5µm, and the thickness of the titanium rhombic mesh support layer is 490µm with a mesh size of 0.5mm×1mm.

[0023] Example 4 The difference between this embodiment and Embodiment 1 is that in step three, the sprayed titanium rhomboid mesh is subjected to a vacuum of 4.6 × 10⁻⁶. -3 Under Pa conditions, the sample was heated to 350℃ at a rate of 1.2℃ / min and held for 6 hours for degreasing, then heated to 1000℃ and held for 4 hours for sintering, and then cooled in the furnace.

[0024] Upon testing, the total thickness of the gas diffusion layer prepared in this embodiment is 133µm, the thickness of the first microporous layer is 12µm with an average pore size of 8µm, the thickness of the second microporous layer is 10µm with an average pore size of 29µm, and the thickness of the titanium rhombic mesh support layer is 110µm with a mesh size of 1mm×3mm.

[0025] Example 5 The difference between this embodiment and Embodiment 1 is that in step three, the sprayed titanium rhomboid mesh is subjected to a vacuum of 7.2 × 10⁻⁶. -3 Under Pa conditions, the sample was heated to 450℃ at a rate of 2℃ / min and held for 10h for degreasing, then heated to 1200℃ and held for 0.5h for sintering, and then cooled in the furnace.

[0026] Upon testing, the total thickness of the gas diffusion layer prepared in this embodiment is 182µm, the thickness of the first microporous layer is 11µm with an average pore size of 9µm, the thickness of the second microporous layer is 11µm with an average pore size of 30µm, and the thickness of the titanium rhombic mesh support layer is 160µm with a mesh size of 0.8mm × 1.5mm.

[0027] Example 6 The difference between this embodiment and Embodiment 1 is that in step three, the sprayed titanium rhomboid mesh is subjected to a vacuum of 7.2 × 10⁻⁶. -3 Under Pa conditions, the sample was heated to 450℃ at a rate of 2℃ / min and held for 10h for degreasing, then heated to 1150℃ and held for 0.5h for sintering, and then cooled in the furnace.

[0028] Upon testing, the total thickness of the gas diffusion layer prepared in this embodiment is 600µm, the thickness of the first microporous layer is 50µm with an average pore size of 10µm, the thickness of the second microporous layer is 50µm with an average pore size of 30µm, and the thickness of the titanium rhombic mesh support layer is 500µm with a mesh size of 0.8mm × 1.5mm.

[0029] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a gas diffusion layer with a gradient pore structure, characterized in that, The gas diffusion layer consists of a first microporous layer, a second microporous layer, and a titanium rhombic mesh support layer bonded together by metallurgy. The preparation method of the gas diffusion layer includes the following steps: Step 1: Immerse the titanium rhombus mesh in liquid paraffin at 70℃~100℃, remove it, cool it, and clean the surface to obtain a titanium rhombus mesh filled with paraffin. Step 2: Anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and two types of spherical titanium powder with different particle sizes are mixed evenly to prepare slurry No. 1 containing fine-grained spherical titanium powder and slurry No. 2 containing coarse-grained spherical titanium powder. Then, slurry No. 2 and slurry No. 1 are sequentially sprayed onto the surface of the titanium rhomboid mesh filled with paraffin in step 1 using a spray gun to obtain the sprayed titanium rhomboid mesh. The concentration of tributyl phosphate in slurry No. 1 and slurry No. 2 is 0.005 g / mL to 0.03 g / mL, the concentration of polyvinyl butyral is 0.03 g / mL to 0.15 g / mL, and the concentration of spherical titanium powder is 0.5 g / mL to 1.5 g / mL. The particle size of the spherical titanium powder in slurry No. 1 is 0.1 µm to 15 µm, and the particle size of the spherical titanium powder in slurry No. 2 is 20 µm to 50 µm. Step 3: The sprayed titanium rhomboid mesh obtained in Step 2 is degreased and sintered in one step to form a first microporous layer with small pore size and a second microporous layer with large pore size, which are then cooled in the furnace to obtain a gas diffusion layer with a gradient pore structure.

2. The method for preparing a gas diffusion layer with a gradient pore structure according to claim 1, characterized in that, In step three, the heating rate for the one-step debinding and sintering process is 0.5℃ / min to 2℃ / min, the debinding temperature is 250℃ to 450℃, the debinding time is 1h to 10h, the sintering temperature is 800℃ to 1200℃, the sintering time is 0.5h to 8h, and the vacuum degree does not exceed 1×10⁻⁶. -2 Pa.

3. A gas diffusion layer with a gradient pore structure prepared according to claim 1 or 2, characterized in that, The total thickness of the gas diffusion layer is 120µm to 600µm, the thickness of the first microporous layer is 10µm to 50µm and the average pore size is 2µm to 10µm, the thickness of the second microporous layer is 10µm to 50µm and the average pore size is 5µm to 30µm, and the thickness of the titanium rhombic mesh support layer is 100µm to 500µm and the mesh size is 0.5mm×1mm to 3mm×5mm.

Citation Information

Patent Citations

  • Preparation method of pore-size-gradient microporous-layer gas diffusion layer

    CN111146467A

  • Powder net composite gas diffusion layer and preparation method and application thereof

    CN115478287A